ETHICAL AND PEDAGOGICAL ASPECTS OF THE INTRODUCTION OF AI IN THE TEACHING OF CULTURE AND ART - Bazar Sultanov (Bright Mind Publishing, 2025)
This article explores the ethical and pedagogical aspects of integrating artificial intelligence (AI) into the teaching of culture and the arts, with a focus on higher education institutions in Uzbekistan. As AI tools become increasingly embedded in educational practice, their use in disciplines traditionally grounded in human interpretation and creativity raises both exciting opportunities and serious concerns. While AI can enhance engagement, personalize learning, and assist in the analysis of cultural artifacts, it also challenges existing pedagogical models and prompts a reconsideration of authorship, originality, and the educator's role. The paper examines the dual nature of AI in this context: as an innovative pedagogical aid and as a technological force requiring thoughtful ethical navigation. Drawing on recent studies, case examples, and theoretical perspectives, the research analyzes how AI applications such as generative models, virtual reality, and datadriven analytics impact teaching methods in art history, music, visual culture, and cultural studies. The article also considers the preparedness of instructors to handle ethical dilemmas, such as bias in AI systems and the risk of over-dependence on technology. Recommendations are offered for educators, policy-makers, and curriculum developers to foster responsible and pedagogically sound integration of AI in the teaching of culture and the arts.
Keywords: Artificial intelligence, pedagogy, ethics, art education, cultural studies, creativity, higher education, digital learning, educational technology.